2005
DOI: 10.1177/0047287505276591
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Distribution Channels: The Visitors’ Perspective

Abstract: This article extends research on tourism distribution channels, a topic dominated by studies of providers and intermediaries, by addressing the use of multiple channels from the visitors’ perspective. The article reports the results of intercept surveys of international and domestic independent visitors, and their use of a range of distribution channels to make travel, accommodation, and attractions arrangements at two New Zealand destinations: Rotorua and Wellington. Emphasis is given in turn to the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 34 publications
(39 reference statements)
6
93
0
5
Order By: Relevance
“…Smith & Xiao suggested that tourism distribution channels could be regarded as different presentation of tourism supply chain for invisibility and complexity of tourism products [6]. Pearce, from view of tourists, adopted field research method to study distribution channels met by tourists in Rotorua and Wellington of New Zealand, which provided a new perspective for improvement of tourism distribution channels [7]. Reid & Pearce studied distribution channels of New Zealand outbound tourism from the perspective of national market, pointing out development trend and challenges of distribution channels [8].…”
Section: Status Of Research On Tourism Distribution Channelmentioning
confidence: 99%
“…Smith & Xiao suggested that tourism distribution channels could be regarded as different presentation of tourism supply chain for invisibility and complexity of tourism products [6]. Pearce, from view of tourists, adopted field research method to study distribution channels met by tourists in Rotorua and Wellington of New Zealand, which provided a new perspective for improvement of tourism distribution channels [7]. Reid & Pearce studied distribution channels of New Zealand outbound tourism from the perspective of national market, pointing out development trend and challenges of distribution channels [8].…”
Section: Status Of Research On Tourism Distribution Channelmentioning
confidence: 99%
“…Some commonalities do occur-especially in terms of package tourism-but important differences are found from sector to sector, market to market, and segment to segment (Stuart, Pearce, & Weaver, 2005;Smith, 2007aSmith, , 2007bSmith & Garnham, 2006;Sharda & Pearce, 2006;Pearce & Sahli, 2007;Pearce, Tan, & Schott, 2004, 2007Schott, 2007). As a result, most suppliers use multi-channel distribution systems and may be faced with a reasonably wide range of alternative channels, more so than in many other sectors where multi-channel distribution is often more recent (Frazier, 1999;Coelho & Easingwood, 2004).…”
Section: The New Zealand Projectmentioning
confidence: 99%
“…In line with much of the wider literature, the customers' viewpoint is subsequently taken as a starting point (Pearce & Schott, 2005;Smith, 2007b), but the needs and behavior of the suppliers and other intermediaries are also explicitly included (Stuart et al, 2005;Pearce, 2007a;510 JOURNAL OF TRAVEL & TOURISM MARKETING Pearce & Sahli, 2007;Pearce & Tan, 2006;Smith, 2007b;Smith & Garnham, 2006;Schott, 2007). Again, these needs and this behavior are travel-specific.…”
Section: The New Zealand Projectmentioning
confidence: 99%
See 2 more Smart Citations